TEACHING EARLY CHILDHOOD TO BE HEALTHY AND CLEAN IN EVERYDAY LIFE - Daviq Chairilsyah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
Living healthily and cleanly is sometimes neglected by parents and teachers to be taught in a programmed and sustainable manner. Teachers often assume that parents have taught hygiene and healthy living habits at home, even though it is not certain that every parent understands the proper way to live healthily and cleanly in early childhood. Meanwhile, parents feel that teachers must have taught clean and healthy lifestyle habits during learning activities at school. In fact, teachers are more preoccupied with children’s learning achievement, which tends to focus on academic knowledge. Using a literature study method, this article aims to assist teachers in understanding the importance and implementation of a clean and healthy lifestyle in early childhood education. The role of kindergarten teachers is to stimulate character education related to healthy and clean living, which should become a priority in all aspects of learning. A clean and healthy lifestyle can be applied in schools through: (1) instilling values of clean and healthy living through health education, (2) carrying out extracurricular activities that incorporate clean and healthy lifestyle behavior values for students, and (3) conducting counseling activities and collaborating with the government health office.